2020
DOI: 10.1136/jramc-2019-001312
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of injuries and factors related to injuries in combat soldiers

Abstract: IntroductionMusculoskeletal injuries to the lower extremities are major factors contributing to drop out from military tasks. The aim of the present study was to determine the incidence of musculoskeletal injuries and the parameters that differentiate between the soldiers who incurred these injuries and those who did not along 14 weeks of an infantry commanders course.MethodsOne-hundred and sixty-eight participants were recruited from an infantry commanders course. The soldiers were tested before (pre), in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Many intrinsic and extrinsic factors have been hypothesised as the cause of overuse injuries, including nutrition,11 fatigue,12 flexibility,11 body mass index,11 13 entry-level fitness,11 14 15 and forces from marching 16–18. A logistic regression model was able to predict musculoskeletal injury, including lower limb overuse injuries, significantly with an accuracy of 34.50% 14.…”
Section: Introductionmentioning
confidence: 99%
“…Many intrinsic and extrinsic factors have been hypothesised as the cause of overuse injuries, including nutrition,11 fatigue,12 flexibility,11 body mass index,11 13 entry-level fitness,11 14 15 and forces from marching 16–18. A logistic regression model was able to predict musculoskeletal injury, including lower limb overuse injuries, significantly with an accuracy of 34.50% 14.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the YBT has been used in several military populations (15,38,41,45) and was found to predict future musculoskeletal injuries (45). Nagai et al (23) reported that reduced static balance was found to be a predictor of future injuries among soldiers, and they suggested that instituting injury prevention programs developed to improve balance might reduce the rate of musculoskeletal injury.…”
Section: Discussionmentioning
confidence: 99%
“…The Y-Balance Test (YBT) for each leg was performed according to the technique of Coughlan et al (7), which was previously published on soldiers (45): After the subject had completed 4 practice trials in each direction on each leg, they were given a 2-minute rest period, then performed 3 test trials in each direction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations